Analysis of the trend of hospitalizations for asthma in children and adolescents in Brazil - Larissa Silva Magalhães; Gabriela Moreira Policena; Viviane Santos Mendes Carneiro; Lusmaia Damaceno Camargo Costa; Maria Selma Neves da Costa; Maria Aparecida da Silva Vieira (Elsevier, 2021)
Objective: To analyze the trend of hospitalizations for asthma in children and adolescents by region and age group in Brazil, from 2008 to 2017. Method: This is a time-series study with secondary data regarding hospitalizations for asthma in children and adolescents, according to age, region, and gender. Descriptive statistics procedures were used with measures of central tendency to calculate the variation between the periods of 2008 and 2017. Rates of hospitalizations were calculated specifically by age group and region. Time trend analysis was performed by simple linear regression, considered as stationary (p > 0.05), declining (p < 0.05 and negative regression coefficient), or ascending (p < 0.05) and positive regression coefficient). Results: The present study identified a higher proportion of hospitalizations for asthma in Brazil in children aged 5-9 years. Regarding gender, there were more hospitalizations in boys. The region that presented the highest proportion of hospitalizations, in all age groups investigated, was the Northeast. As for the trend analysis, this article showed that, in Brazil, there was a trend toward a reduction in hospitalization rates for asthma. Conclusion: In Brazil, there was a tendency to reduce hospitalizations for all investigated age groups. The Northeast was the only region that showed a decline in all age groups.